Development and Validation of an Integrated Electronic Patient Progress Note-Based Healthcare Evaluation Instrument for Diabetes Management - István Fedor; Taisia Chertenko; Junhong Kim (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This research sought to design and rigorously evaluate an Integrated Electronic Progress Note instrument intended to support frailty risk monitoring and strengthen care coordination among older adults. Methodology: A methodological research approach was undertaken, beginning with conceptual framework development and item generation, followed by expert review for content adequacy and empirical validation. Data were obtained from 210 healthcare professionals alongside 320 de-identified electronic progress notes collected at Uzsoki Street Hospital. Psychometric evaluation included content validity indexing, internal consistency assessment, and construct validation using Partial Least Squares Structural Equation Modeling with bootstrapping procedures to test structural relationships. Main Findings: The developed instrument demonstrated high content agreement among experts (S-CVI = 0.93) and strong reliability indicators, with composite reliability values exceeding 0.90. Convergent validity met recommended thresholds (AVE > 0.50), while discriminant validity was confirmed through HTMT ratios below 0.90. The structural analysis indicated that the model accounted for 68% of the variance in documentation quality (R² = 0.68) and showed meaningful predictive capability (Q² = 0.49). Among the examined constructs, Care Coordination exerted the most substantial positive influence on documentation quality (β = 0.41, p < 0.001). Furthermore, improved documentation performance was significantly linked to a lower likelihood of 30-day readmission (β = –0.32, p < 0.01). Novelty/Originality of this study: This study presents a validated multidimensional measurement tool that connects frailty risk assessment elements with the quality evaluation of electronic clinical documentation, thereby advancing the integration of geriatric clinical assessment and digital health governance frameworks.